The Effect of Quick Ratio and Cash Ratio on Current Ratio in Retail Companies on The Indonesia Stock Exchange (International Journal of Economics Management and Social Science, 2025)
This study aims to analyze the effect of Quick Ratio and Cash Ratio on Current Ratio in retail companies listed on the Indonesia Stock Exchange (IDX) during the period 2014–2024. The background of this study is based on the importance of understanding the fundamental factors that influence liquidity in the competitive retail sector. The method used is multiple linear regression analysis based on 33 observations from three companies: PT Ramayana Lestari Sentosa Tbk, PT Matahari Department Store Tbk, and PT Mitra Adiperkasa Tbk. Classical assumption tests were conducted to test the validity of the model, including normality tests (histogram, Normal PP Plot, skewness, kurtosis), multicollinearity (VIF < 10), autocorrelation (Durbin-Watson), and heteroscedasticity (scatterplot and Glejser test). The results show that the regression model is statistically significant with an R Square value of 97.0%, and meets all basic assumptions except the Durbin-Watson test which is inconclusive. Partially, Quick Ratio has a positive and significant effect on Current Ratio, while Cash Ratio has no significant effect. This study concludes that the Quick Ratio is a key indicator in assessing the liquidity of retail companies. Therefore, companies are advised to improve the efficiency of managing receivables and operational cash to maintain sustainable financial health.